2017
DOI: 10.1080/0284186x.2017.1400685
|View full text |Cite|
|
Sign up to set email alerts
|

COX-2 expression and effects of celecoxib in addition to standard chemotherapy in advanced non-small cell lung cancer

Abstract: In this subgroup analysis of patients with advanced NSCLC treated within the context of a randomized trial, we could not detect any interaction effect of COX-2 expression in tumor or stromal cells and the outcome of celecoxib treatment in addition to standard chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Both celecoxib and pantoprazole are FDA-approved common drugs. Celecoxib, as a nonsteroidal anti-inflammatory drug, was reported to be used in the treatment of NSCLC due to the relationship between cancer and inflammation 31 . Moreover, pantoprazole was considered to increase the sensitivity of drug-resistant cancer cells such as lymphomas and gastric adenocarcinomas 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Both celecoxib and pantoprazole are FDA-approved common drugs. Celecoxib, as a nonsteroidal anti-inflammatory drug, was reported to be used in the treatment of NSCLC due to the relationship between cancer and inflammation 31 . Moreover, pantoprazole was considered to increase the sensitivity of drug-resistant cancer cells such as lymphomas and gastric adenocarcinomas 32 .…”
Section: Discussionmentioning
confidence: 99%
“…It prevents metastatic progression, which provides additional support for the role of COX-2 in EMT induction. Conversely, some clinical trials have shown that the COX-2 inhibitor, celecoxib, is effective at controlling tumor progression [156,157]. This discrepancy may be due to the differences between these two inhibitors and their underlying molecular mechanisms.…”
Section: Clinical Significance Of Metabolic Regulation In Cancer Tmentioning
confidence: 99%
“…These inconsistent results and the fact that COX-2 expression in tumor or stromal cells has no impact on the effect of celecoxib ( 39 , 41 ) may be explained by the various expression patterns of the downstream PGE2 receptors, which vary between organs and cell lines ( 42 ). Multiple HNSCC cell lines have been reported with wide variation of EP expression patterns ( 14 , 43 ).…”
Section: Discussionmentioning
confidence: 99%